The Relationship of the Self to the Other in Michel Foucault - كحيله, غياث (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is concerned with examining the subject of the relationship between the self and the other as outlined and defined by the French philosopher Michel Foucault, from two perspectives, one ethical and the other non-ethical. If the relationship of the self to the other from an ethical perspective emerged in ancient philosophies, especially Greek and Hellenistic-Roman, and if this relationship took on several dimensions among the Greeks, the most prominent of which was the teleological dimension, such that the self's orientation to the other became the goal and objective that it seeks to achieve through its orientation and turning towards itself, and if this relationship took on an implicit dimension in the Hellenistic-Roman era, closest to immanence, such that the self's movement towards the other became implicit and immanent to its movement and orientation towards itself. In contrast, the relationship of the self to the other from an unethical perspective emerged in modern philosophy, taking on an exclusionary dimension represented in a set of authoritarian and exclusionary measures that the self-practiced against the other. The relationship between the self and the other, as defined by Foucault, is situated within the context of self-formation and construction. This formation can occur either in an ethical manner or in a non-ethical manner, as previously mentioned. This means that the relationship between the self and the other is determined and its contours are drawn according to these two processes of self-formation and construction. In this sense, we can discuss the relationship between the self and the other according to Foucault based on these two paths. The importance of this research lies in its attempt to provide a study that sheds light on the discourse presented by Michel Foucault regarding the relationship between the self and the other, both ethically and non-ethically, with the aim of unveiling the new insights he offered in comparison to those who have analyzed and investigated this topic.